Republic of Korea : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses key findings of the Report on the Observance of Standards and Codes for the Republic of Korea. Responsibilities, objectives, and powers related to banking supervision are clearly defined in the Republic of Korea. The legal framework currently in place reasonably provides the necessary powers to authorize the establishment of banks, conduct ongoing supervision, address compliance with laws and regulations, as well as undertake corrective actions to address safety and soundness concerns. Authorization processes are generally thorough but there is room to require formal approval for certain activities.